INFRASTRUCTURE FACILITY NEEDS ANALYSIS CITY PARK IN THE NEW NORMAL ERA : (CASE STUDY: TAMAN ADIPURA MUARA ENIM) - Mita Hargianti; Nasution Nasution; Husnul Hidayat (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
City parks are again crowded with people after COVID-19 to play, exercise and recreation, and Adipura Muara Enim Park is no exception. The Covid-19 pandemic is not certain to end. For this reason, the facilities available in city parks in the new normal era need to be conditioned so that they can provide optimal services and can support the government's efforts in handling COVID-19. The aim of the research is to analyze the need for infrastructure facilities and get the "level of service" (LOS). The research used a descriptive survey data collection method in the form of observing physical settings, functional aspects and similar research theories and then distributing questionnaires with several variables, namely the level of service facilities, level of activity level, significance and level of ease of achievement. Attitudes were assessed using a Likert scale and the "level of service" (LOS) analysis method. The results showed that the level of service at Adipura Muara Enim Park was F (< 5), that is, there was an accumulation of user activity due to the uneven distribution of facilities. It is necessary to add and adjust the facility design to meet the new normal criteria, including: the addition of an outdoor gym, guard post, information media boards, hand washing facilities, body temperature measuring device, pavement material pattern as a spacer, single seats, vegetation as a barrier between facility.